From the Ace Ventura when nature calls soundtrack : spirits in the material world - MCA Records; Morgan Creek Productions (California : MCA Records, 1995)
Contains the song from the soundtrack of Ace Ventura When Nature Calls movie.
CD 1 : Spirits In The Material World (LP Version) / (4:38) -- Spirits In The Material World (Instrumental) / (4:38).
Koleksi Khas Wiramanja.
Performers: Pato Banton with Sting.
Title from disc label.
Keywords: Motion picture music; Film soundtracks